Optimal allocation of distributed generators providing reactive power support ancillary service - Rueda-Medina, A. C. [UNESP]; Padilha-Feltrin, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Problems as voltage increase at the end of a feeder, demand supply unbalance in a fault condition, power quality decline, increase of power losses, and reduction of reliability levels may occur if Distributed Generators (DGs) are not properly allocated. For this reason, researchers have been employed several solution techniques to solve the problem of optimal allocation of DGs. This work is focused on the ancillary service of reactive power support provided by DGs. The main objective is to price this service by determining the costs in which a DG incurs when it loses sales opportunity of active power, i.e, by determining the Loss of Opportunity Costs (LOC). The LOC will be determined for different allocation alternatives of DGs as a result of a multi-objective optimization process, aiming the minimization of losses in the lines of the system and costs of active power generation from DGs, and the maximization of the static voltage stability margin of the system. The effectiveness of the proposed methodology in improving the goals outlined was demonstrated using the IEEE 34 bus distribution test feeder with two DGs cosidered to be allocated. © 2011 IEEE.
Keywords: Distributed generators; multi-objective optimization; optimal allocation; reactive power support; Active power; Active power generation; Ancillary service; Fault conditions; Multi objective; Opportunity costs; Optimal allocation; Optimization process; Power-losses; Reliability level; Sales opportunities; Solution techniques; Static voltage stability margin; Test feeders; Costs; Distributed power generation; Power quality; Reactive power; Sustainable development; Voltage stabilizing circuits; Multiobjective optimization